Recent Advances in Photoredox Catalysis Enabled Functionalization of α-Amino Acids and Peptides: Concepts, Strategies and Mechanisms - Liu, Jian-Quan; Shatskiy, Andrey; Matsuura, Bryan S.; Kärkäs, Markus D. (Synthesis, 2019)
The selective modification of α-amino acids and peptides constitutes a pivotal arena for accessing new peptide-based materials and therapeutics. In recent years, visible light photoredox catalysis has appeared as a powerful platform for the activation of small molecules via single-electron transfer events, allowing previously inaccessible reaction pathways to be explored. This review outlines the recent advances, mechanistic underpinnings, and opportunities of applying photoredox catalysis to the expansion of the synthetic repertoire for the modification of specific amino acid residues.1 Introduction2 Visible-Light-Mediated Functionalization of α-Amino Acids2.1 Decarboxylative Functionalization Involving Redox-Active Esters2.2 Direct Decarboxylative Coupling Strategies2.3 Hypervalent Iodine Reagents2.4 Dual Photoredox and Transition-Metal Catalysis2.5 Amination and Deamination Strategies3 Photoinduced Peptide Diversification3.1 Gese-Type Bioconjugation Methods3.2 Peptide Macrocyclization through Photoredox Catalysis3.3 Biomolecule Conjugation through Arylation3.4 C–H Functionalization Manifolds4 Conclusions and Outlook
Keywords: amino acids; electron transfer; peptides; photoredox catalysis; radicals; visible light